2017
DOI: 10.24966/fsn-1076/100026
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Lactic Acid Bacteria Strains from Raw Camel Milk for Potential Use in the Production of Yogurt

Abstract: The objective of this work is to formulate a starter lactic seen application camel milk to prepare fermented product yoghurt. Lactic acid bacteria isolated from camel milk has different characterization tests and selection: morphological study, catalase test, gram stain, use of citrate, acidifying power, lipolytic power and proteolytic power. These tests have to choose the strains: 1, 4, 5, 6, 7, 8, 9 and 10 which has ΔpH ≥ 0.3U after 6h as the most acidifying and EPS producing strains. All the strains showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…However, their survival rate after freeze-drying ranges from 60.7 to 83.3%. This finding is supported by other studies which reported that the survival of LAB after freeze-drying seemed to be strain dependent (Edward et al, 2010;Fguiri et al, 2017). The main reasons for this variation could be the nature of the strains, the age of the culture, cell concentration, the type of cryoprotectants used, and cell damage at the cell wall and cell membrane.…”
Section: Properties Of Starter Culturessupporting
confidence: 83%
“…However, their survival rate after freeze-drying ranges from 60.7 to 83.3%. This finding is supported by other studies which reported that the survival of LAB after freeze-drying seemed to be strain dependent (Edward et al, 2010;Fguiri et al, 2017). The main reasons for this variation could be the nature of the strains, the age of the culture, cell concentration, the type of cryoprotectants used, and cell damage at the cell wall and cell membrane.…”
Section: Properties Of Starter Culturessupporting
confidence: 83%
“…The production of bioactive substances by the six obtained lactic bacteria (B1, B2, B3, B4, B5, and B6) showed that all bacteria were able to inhibit the growth of A. flavus in vitro (Figure 3 The antifungal activity of Lactobacillus strain against toxigenic fungi was elaborated in several studies, in fact, LAB were isolated from the breast milk. Their antifungal activity against A. flavus producing aflatoxin was investigated with four methods, in the case of seven isolated LAB (Fguiri et al, 2017). In addition, Gerbaldo et al (2012), confirmed that Lactobacillus rhamnosus L60 and Lactobacillus fermentum L23 are the most producing of secondary metabolites, such as organic acids, bacteriocins, and hydrogen peroxide.…”
Section: Selection Of Bacterial Isolates With Antifungal Effectmentioning
confidence: 75%
“…Their antifungal activity against A . flavus producing aflatoxin was investigated with four methods, in the case of seven isolated LAB (Fguiri et al, ). In addition, Gerbaldo et al (), confirmed that Lactobacillus rhamnosus L60 and Lactobacillus fermentum L23 are the most producing of secondary metabolites, such as organic acids, bacteriocins, and hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterilized skim milk 10% (w/v) was inoculated with 3% from each isolate and fermented at 37 °C until the medium gets coagulated (Fguiri et al, 2017). The pH of the samples was monitored at 0 hour, 2 hours, 4 hours, 6 hours and after 24 hours (during the fermentation period) using a digital pH meter (Thermo Scientific/Orion 3 STAR pH Bench top) calibrated with buffers at pH 4.0 and 7.0.…”
Section: Detection Of Fermentation Abilities Of the Isolatesmentioning
confidence: 99%